Predisposing factors to severe external root resorption associated to orthodontic treatment - Picanço,Gracemia Vasconcelos (2013)
OBJECTIVE: The aim of this study was to evaluate predisposing factors among patients who developed moderate or severe external root resorption (Malmgren's grades 3 and 4), on the maxillary incisors, during fixed orthodontic treatment in the permanent dentition. METHODS: Ninety-nine patients who underwent orthodontic treatment with fixed edgewise appliances were selected. Patients were divided into two groups: G1 - 50 patients with no root resorption or presenting only apical irregularities (Malmgren's grades 0 and 1) at the end of the treatment, with mean initial age of 16.79 years and mean treatment time of 3.21 years; G2 - 49 patients presenting moderate or severe root resorption (Malmgren's grades 3 and 4) at the end of treatment on the maxillary incisors, with mean initial age of 19.92 years and mean treatment time of 3.98 years. Periapical radiographs and lateral cephalograms were evaluated. Factors that could influence the occurrence of severe root resorption were also recorded. Statistical analysis included chi-square tests, Fisher's exact test and independent t tests. RESULTS: The results demonstrated significant difference between the groups for the variables: Extractions, initial degree of root resorption, root length and crown/root ratio at the beginning, and cortical thickness of the alveolar bone. CONCLUSION: It can be concluded that: Presence of root resorption before the beginning of treatment, extractions, reduced root length, decreased crown/root ratio and thin alveolar bone represent risk factors for severe root resorption in maxillary incisors during orthodontic treatment.